MODEL AGROKONSERVASI UNTUK PERENCANAAN PENGELOLAAN DAS GARANG HULU - Dewi Liesnoor Setyowati; Mohammad Amin; Erni Suharini; Bitta Pigawati (TATALOKA, 2012)
The problems in the Garang Watershed includes flooding, erosion, sedimentation, landslides, and droughts. It can be overcome by the land uses arrangement. Management in Garang Watershed can be planned using agro-conservation model. This model consists of three submodels, i.e., water management submodel,  erosion submodel, and community submodel. Submodel water management produces TATAAIR.EXE software, used for the simulation of optimal land use planning. Addition 10% of the forest area and 10% mixed farms are  the most optimal landuse composition, whereas 25% of forest reduction to moor can increase the ratio of discharge and water production. The total value of actual erosion in Upstream Garang Watershed is 3249.861 tonnes/ha/year. Level of erosion hazard are height erosion which cover area of 27.20%, moderate erosion covers area of 21.57%, and mild erosion covers area of 38.86%. Forms of conservation for the handling of the dangers of erosion that can be done include: vegetative engineering, vegetative-mechanic engineering, and without conservation measures. Environmentally conscious community forum should be established at least at the level of RW as a cadre to increase public awareness in preserving the environment.